Effectiveness of Different Modalities of Lip Repositioning Surgery for Management of Patients Complaining of Excessive Gingival Display: A Systematic Review and Meta-Analysis. (7th October 2021) - Younespour, Shima; Yaghobee, Siamak; Aslroosta, Hoori; Moslemi, Neda; Pourheydar, Elham; Ghafary, Elaha Somaya
Abstract : Purpose . This study is aimed at synthesizing the available evidence regarding effectiveness of various modalities (combinations of LRS tasks) and comparison between each two modalities in terms of gingival display reduction, success rate, stability of the results, patient's satisfaction, and postoperative morbidity. Materials and Methods . The electronic databases including PubMed, Scopus, Web of Science Cochrane Library, Google Scholar databases, ClinicalTrials.gov, and WHO International Clinical Trial Registry Platform were searched up to 27th June 2020 regarding lip repositioning surgery. The modalities were defined as the combinations of the following tasks: frenectomy (yes/no), flap thickness (full/partial), and myotomy (yes/no). Meta-analyses were performed on gingival display change from baseline to months 3, 6, and 12 in each modalities using Stata (v.16). Results . 38 studies (including three clinical trials, two quasiexperimental studies, seven case series, and 26 case reports) met the criteria for final inclusion. The mean gingival display reduced from baseline to 6 months (WMD = − 2.90, 95% CI: -4.85 to -0.95) in the patients undergoing the "frenectomy + full-thickness flap + myotomy" modality. This parameter decreased from baseline to 6 and 12 months, respectively (WMD = − 2.68, 95% CI: -3.49 to -1.86; WMD = − 2.52, 95% CI: -4.40 to -0.64), in patients undergoing the "frenectomy + partial-thickness flap + without myotomy" modality. In patients who undergone the "without frenectomy + partial-thickness flap + without myotomy" modality, gingival display reduced from baseline to 6 months (WMD = − 3.22, 95% CI: -5.61 to -0.84). Almost 83% of patients with modality 1 had satisfaction. Conclusions . Gingival display within the 6 months after LRS could be reduced with all modalities. Descriptively, the greatest reduction was observed in patients with the modality not including the frenulum.